Significant impact of bleaching treatment on phage-host interaction dynamics in a full-scale wastewater treatment plant - Peihan Yan; Junge Zhu; Qianwei Ji; Gaolin Hou; Guoqiang Liang; Xinchun Liu; Ruyin Liu (Scientific Reports)
Abstract The temporal dynamics of phage-host interactions within full-scale biological wastewater treatment (BWT) plants remain inadequately characterized. Here, we provide an in-depth investigation of viral and bacterial dynamics over a nine-year period in an activated sludge BWT plant, where bleach addition was applied to control sludge foaming. By conducting bioinformatic analyses on 98 metagenomic time-series samples, we reconstructed 3,486 bacterial genomes and 2,435 complete or near-complete viral genomes, which were classified into 361 bacterial and 889 viral clusters, respectively. Our results demonstrate that the primary bleaching event induced significant shifts in both bacterial and viral communities, as well as in virus-host interactions, as evidenced by alterations in bacteria-virus interaction networks and virus-to-host ratio dynamics. Following bleaching, the bacteria-virus network became less interconnected but more compartmentalized. Viral communities mirrored bacterial dynamics, indicating a strong coupling in phage-host interactions. Among the identified virus-host pairs, many exhibited a decelerating rise in viral abundance relative to host abundance, with virus-to-host ratios generally displaying a negative correlation with host abundance. This trend was particularly pronounced in virus-host pairs where viruses harbored integrase genes, indicative of temperate dynamics resembling a “Piggyback-the-Winner” model. Notably, the bleaching intervention appeared to induce a transition from lysogeny to lysis in viruses associated with some foaming-related bacterial species, suggesting a potential virus-involved indirect mechanism by which bleaching mitigates sludge foaming.